If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.12 + -0.02(x + 3) = -0.01(3 + -1x) Reorder the terms: 0.12 + -0.02(3 + x) = -0.01(3 + -1x) 0.12 + (3 * -0.02 + x * -0.02) = -0.01(3 + -1x) 0.12 + (-0.06 + -0.02x) = -0.01(3 + -1x) Combine like terms: 0.12 + -0.06 = 0.06 0.06 + -0.02x = -0.01(3 + -1x) 0.06 + -0.02x = (3 * -0.01 + -1x * -0.01) 0.06 + -0.02x = (-0.03 + 0.01x) Solving 0.06 + -0.02x = -0.03 + 0.01x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.01x' to each side of the equation. 0.06 + -0.02x + -0.01x = -0.03 + 0.01x + -0.01x Combine like terms: -0.02x + -0.01x = -0.03x 0.06 + -0.03x = -0.03 + 0.01x + -0.01x Combine like terms: 0.01x + -0.01x = 0.00 0.06 + -0.03x = -0.03 + 0.00 0.06 + -0.03x = -0.03 Add '-0.06' to each side of the equation. 0.06 + -0.06 + -0.03x = -0.03 + -0.06 Combine like terms: 0.06 + -0.06 = 0.00 0.00 + -0.03x = -0.03 + -0.06 -0.03x = -0.03 + -0.06 Combine like terms: -0.03 + -0.06 = -0.09 -0.03x = -0.09 Divide each side by '-0.03'. x = 3 Simplifying x = 3
| 25*34= | | 49x1/4 | | 2Y-8=3y-8 | | 7x-6/x=1 | | .6x+.9=.8x-.7 | | .8x-4.6=.2 | | 8=6x+4x | | .16(y-2)+.12y=.2y-.6 | | 5x+5=-4+2x+21 | | 5n-n=48 | | 5(3n+3)=7(7n+4)+2 | | 2x+5+7=18 | | -9y-14=7y+18 | | 28-4x=10-7x | | 4n/3=3n/10 | | (7/y-8)-(6/8-y) | | 8(6x-7)=50 | | -5y-13=4y+14 | | -4(3t-3)+6t=5t-2 | | 4+3x=-6+x | | -2x-6x-5= | | X*.20=23.04 | | r(c-5)+s(c-4)=0 | | 3(n+15)=-45 | | 4x-3(5x+1)=18-2x+3 | | 4[5-4(4-t)]-3=5[4(5t-3)+9]-63 | | -5t^2-20t-25=0 | | 17x+45=37x-33 | | -7x+6=-9x-2 | | 3(2m-3)-4(m+4)= | | F(x)=9-2(4) | | n+4=n |